Heterogeneity of ventricular action potentials in neonatal rat cardiomyocytes and methodological aspects of patch clamp measurements - Syren, Pascal; Zlatopolskaia, Anna; Bruehl, Claus; Schöffel, Axel; Caspari, Teresa; Heß, Chiara; Frey, Norbert; Thomas, Dierk; Lugenbiel, Patrick (Frontiers in Physiology, 2025)
Measurement of the ventricular action potential (AP) via whole-cell patch clamp is an important contributor to cardiac electrophysiological research. Neonatal rat ventricular cardiomyocytes (NRVCM) are a commonly used model, in particular for stressor- or drug-related questions. High variability of APs and individual methodological settings hinder comparison both in individual studies and, to an even greater degree, between different projects. This study aims to describe sources of AP heterogeneity in NRVCM related to patch clamp measurement with a focus on resolvable causes. Therefore, AP of NRVCM were induced in whole-cell configuration and measured in current-clamp mode. The effects of varying setup temperature, electrode resistance, resting- (RMP), respectively holding membrane potential (HMP), induction approach, current pulse duration and amplitude plus total assay duration were studied and compared to systematically analyzed literature. We analyzed the impact on different output parameters, namely, maximal upstroke velocity (dV/dt), maximal AP amplitude (APA) and AP duration at different percentages (XX%) of repolarization, APDXX. In a comparative literature research, we found that mean APD90 in between 27.0 and 560.7 ms (own data 59.7 ± 5.8 ms) were described, with high variability and likely non-Gaussian distribution. In this study, APD90, APD50 and APD30, are decreased at more negative RMP (respectively HMP) values. E.g., APD90 is shortened by ∼60% after lowering HMP from −70 mV to −90 mV) while dV/dt and APA are increased at a more negative HMP. Pulse duration in induction did not affect main AP parameters itself, but induction energy levels above 1.5-fold the threshold energy level increased APA, while APD50 and APD90 were shortened. During series of APs at 1 Hz, spike duration (APD90) decreased by ∼27%, with stable AP after the third repetitive AP. Spike duration did also decreased by ∼40% after prolongated measurements for 21 min, indicating degradation of electrophysiological properties. To improve data quality in NRVCM-APs, we suggest using a constant HMP, adjustment of current pulse amplitude to the individual cells’ threshold and the use of repetitive AP-inductions. Finally, we suggest the use of nonparametric statistical methods for statistical analysis. These aspects could reduce variability and lead to more reliable and comparable data.